Factors Associated with Nutritional Status of the Under Five Children - Pradhan, Amita (Asian Journal of Medical Sciences, 2010)
Objective: To identify factors associated to the nutritional status of under five children. Method: The data used in this analysis are from Demographic and Health Survey 2006 conducted in Nepal. Total 5262 cases are included in the present study. A multinomial logistic regression model is used to study the relation between various factors and nutritional status. Results: Increasing body mass index of mothers and wealth index shows decreasing likelihood of malnutrition among children. Rural children show insignificant higher likelihood of different forms of underweight and wasting as compared to urban area. Frequency of listening radio does not show significant association in case of mild and moderate wasting and shown very high unusual odds ratio in case of severe wasting. Similarly, lower frequency of watching television also does not show significantly higher likeliness of different form of stunting, underweight and wasting. Female children are more likely to be stunted, underweight and wasted as compared to male. Female headed households are more likely to have moderately and mildly stunted children and mixed results are observed for underweight and wasting. The likelihood for all forms of malnutrition is higher among children with smaller than average size at birth as compared to average or bigger size at birth. Mixed results are observed regarding likelihood of different forms of malnutrition among children with mothers having different educational level. Conclusion: Body mass index of mothers is found significant variable while explaining children's nutritional status. Similarly, Size at birth is significantly associated with nutrition during the childhood. Keywords: Stunting; wasting; under weight; under five children DOI: 10.3126/ajms.v1i1.2927 Asian Journal of Medical Sciences Vol.1(1) 2010 p.6-8